ASSESSMENT OF THE ROLE OF MORINGA OLEIFERA SEEDS POWDER IN THE PURIFICATION OF WASTEWATER FROM THE NIGERIAN BREWERIES, KADUNA NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Brewery wastewater produces effluent that is characterized with high turbidity, pH, biological oxygen demand, chemical oxygen demand and brownish black colour, this effluent is released into the environment indiscriminately. The study investigated the effectiveness of Moringa oleifera seeds powder in purification ofBreweries wastewater. Laboratory jar test experiment was carried out on the wastewater using the coagulation - flocculation – sedimentation sequence. The descriptive statistics using mean and graphs was used. Results were obtained from the different dosages of Moringa oleifera seeds powder ranging from 20 gto 120 g in the wastewater. Optimum dosage for Turbidity, pH, biological oxygen demand, chemical oxygen demand and colour reduction in the treated water was determined. It was observed that at 120 g dose, the Moringa oleifera seeds powder possesses greater efficiency in reducing the tested parameters. The results show that the initial brownish black colour of the raw water has changed to colourless after treatment. The initial pH, turbidity, biological oxygen demand and chemical oxygen demand, of 4.17, 29 NTU, 2177.8 5mg/l and 7137.67 mg/l also reduces to 6.85, 9 NTU, 20 mg/l, and 890 mg/l respectively. This shows that the Moringa oleifera seeds powder has the potentials for treatment of wastewater; and is effective in purifying wastewater from the Nigerian Breweries, Kaduna. For cheaper coagulant, it is therefore more economical to use moringa oleifera in treatment of wastewater
Keywords: Brewery, coagulation Moringa oleifera, treatment, wastewater